NGHIÊN CỨU SẢN XUẤT DẦU BÔI TRƠN CHO QUÁ TRÌNH CÁN KÉO DÂY KIM LOẠI - Kha, Đinh Văn (Vietnam Journal of Science and Technology, 2012)
Researching lubricant oil for metal rolling and drawing has great significance in metallurgical technology and metal processing. According to each application, the lubrication is prepared with suitable ratios of mineral oils, vegetable oils (including peanut oil and rubber seed oil) and anti-oxidants, corrosion inhibitors, emulsifiers, EP additives. Actual effect of the lubricants is demonstrated by feature testing methods and practice results.